EFFICACY EVALUATION OF PROBIOTIC LACTOBACILLUS RHAMNOSUS SUSPENSION FORMULATED WITH MEDIUM CHAIN TRIGLYCERIDES OIL IN DNBS-INDUCED COLITIS IN SPRAGUE-DAWLEY RATS (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Inflammatory bowel disease (IBD) is a highly prevalent chronic inflammatory disease condition leading to widespread gastrointestinal tract (GIT) damage. Based on the severity, the symptoms of IBD vary ranging from mild and frequent abdominal pain, bloating, and diarrhea to severe bloody stools, anemia, unconsciousness, and sometimes fatal as well. Gut dysbiosis is found to play one of the major roles in the pathogenesis of IBD. The current study aimed to evaluate the effectiveness of a probiotic (Lactobacillus rhamnosus) suspension in medium-chain triglycerides (MCT) oil against dinitrobenzene sulfonic acid (DNBS) induced colitis in rats. Colitis was induced in Sprague Dawley (SD) rats by intra-rectal administration of DNBS (120 mg/kg/rat) followed by 3 days of colitis induction. Following colitis induction, rats were evenly randomized to receive either dexamethasone (2 mg/kg/day orally) or L. rhamnosus oil suspension (3 x 106 CFU/g/day orally) for 28 consecutive days. The body weight, average food, and water intake, histological analysis, colon weight, biomarkers of oxidative stress (nitric oxide (NO) and malondialdehyde (MDA)), intestinal inflammation (fecal calprotectin), and antioxidant potential (glutathione (GSH) and superoxide dismutase (SOD)). The level of colonic damage was evaluated using the colonic mucosal damage index (CMDI) and disease activity index (DAI) scores. GraphPad Prism software was used for statistical analysis with p < 0.05 as the significance threshold. Dexamethasone and L. rhamnosus oil suspension significantly prevented body weight and food and water intake reduction. Similarly, dexamethasone and L. rhamnosus oil suspension therapy significantly attenuated the DNBS-induced colonic damage level. This effect was accompanied by significant improvement in the antioxidant biomarker levels (GSH and SOD) and reduction in the oxidative stress and intestinal inflammation level. In all the evaluated parameters, dexamethasone therapy significantly better than the L. rhamnosus oil suspension therapy. The results of this study highlight the protective effect of dexamethasone and L. rhamnosus oil suspension therapy in a DNBS-induced experimental colitis model, an effect that might be attributed to the therapies' antioxidant and anti-inflammatory potential.